Minimum Wages and Restaurant Employment for Teens and Adults in Metropolitan and Non-metropolitan Areas - John V. Winters (Institute of Labor Economics (IZA), 2022)
This study estimates effects of minimum wages on individual restaurant employment using the 2005-2019 Current Population Survey (CPS) and a two-way fixed effects regression model. I examine effects for teens and adults with less than an associate's degree for the entire U.S. and by metropolitan area status. The results indicate that minimum wages on average decrease restaurant employment for teens and increase restaurant employment for these adults, suggesting that minimum wages induce labor-labor substitution. However, this pattern is driven by metropolitan areas residents. The estimated coefficient for minimum wages on teen restaurant employment in non-metropolitan areas is not statistically significant.
Keywords: J20; J30; R10; 330; minimum wages; restaurants; employment; teens